A study on metabolic healthy obesity and its risk of chronic kidney disease - LIANG Qiao-jing; ZHANG Guo-juan; HUANG Wen; JIANG Li-ping; WANG Ning-li (Linchuang shenzangbing zazhi)
Objective Metabolic healthy obesity is a special phenotype with normal metabolic state and insulin sensitivity.Whether this type of obesity increases the risk of chronic kidney disease is unclear.The purpose of this study was to investigate the relationship between metabolic healthy obesity and the risk of chronic kidney disease(CKD).Methods With the population in rural region of Handan,Hebei Province as the study object for a cross-sectional study,with BMI≥25 kg/m~2 defined as obesity,by defining metabolic syndrome with the diagnosis criteria in the third report of the adult group in the national cholesterol education plan,the study population was divided into four groups:MHNO(Metabolically Healthy Nonobesity),MHO(Metabolically Healthy Obesity)and MUNO(Metabolically Unhealthy Nonobesity),MUO(Metabolically Unhealthy aspect).The prevalence of chronic kidney disease in each group was summarized and risk factors of CKD were analyzed by Logistic model.Results A total of 5 429 subjects were enrolled in this study,the prevalence of CKD was 17.5%,and the MHO group had 770 subjects,accounting for 34.4% of the obesity population.Compared with the MHNO group,the level of urinary protein in the MHO group was lower(21.14±58.83 vs.31.37±180.67,P=0.026),and there were no statistically significant differences between the two groups in eGFR(98.04±15.29 vs.98.17±13.92,P=0.822)and the prevalence of CKD(14.7% vs.15.2%,P=0.769).The multivariate Logistic regression model showed that the risk factors for CKD included age,female,metabolic syndrome and coronary heart disease.With the MHNO group as reference,the OR for CKD in the MHO group was 0.96(95%CI 0.762～1.211,P=0.731),and ORs in the MUNO group and MUO group were 1.478(95%CI 1.233～1.788,P=0.000)and 1.381(95%CI 1.161～1.644,P=0.000),respectively.After correcting age,sex and factors of coronary heart disease,the OR in the MHO group was 0.961(95%CI 0.760～1.215,P=0.737),and the values in the MUNO group and MUO group were 1.240(95%CI 1.012～1.518,P=0.038)and 1.234(95%CI 1.028～1.480,P=0.024),respectively.Conclusions There is no significant correlation between metabolically healthy obesity and CKD,and the risk of CKD in metabolically healthy obese population is similar to that in metabolically healthy and normal-weight population.Metabolic syndrome is significantly associated with an increased risk of chronic kidney disease,and the risk of chronic kidney disease is significantly higher in the population with metabolic abnormalities and normal weight than in the one with metabolic health and obesity.